Nowe życie uczniów Jezusa w Ewangelii Jana - Ledwoń, Dawid (Collectanea Theologica, 2018)
This short study of the narration and theology of the Fourth Gospel focuses on the apparently absent, yet undeniably visible theme of the new life of the disciples of Jesus, which He himself defines as the knowledge of the Father and the Son (17,3). The various stages of the analysis of John’s text are aimed at establishing the reasons, the time frame, the environment of the addressees, and the nature of the change, which allows the life of the disciples to be described as new. The study ends with a presentation of the laws and the rules defining the meaning of the new life with a short reference to the present times.